2004
DOI: 10.1007/s00468-003-0305-8
|View full text |Cite
|
Sign up to set email alerts
|

Heartwood and sapwood development within maritime pine ( Pinus pinaster Ait.) stems

Abstract: Heartwood and sapwood development in maritime pine (Pinus pinaster Ait.) is reported based on 35 trees randomly sampled in four sites in Portugal. It was possible to model the number of heartwood rings with cambial age. The heartwood initiation age was estimated to be 13 years and the rate of sapwood transformation into heartwood was 0.5 and 0.7 rings year 1 for ages below and above 55 years, respectively. Reconstruction of heartwood volume inside the tree stem was made by visual identification by image analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
52
2
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 19 publications
11
52
2
4
Order By: Relevance
“…54% of the cross-section at the 5% height level, values somewhat higher than the 42% found by Gominho and Pereira [8] for 9-year-old E. globulus trees, but lower than the 73% found by Miranda et al [18] for 18-year-old E. globulus trees. This indicates the role of tree age in increasing the heartwood proportion as has been referred, too for E. grandis [2], Populus tremuloides [29], Pseudotsuga menziesii [13], Abies balsamea [11] and Pinus pinaster [21].…”
Section: Sitementioning
confidence: 67%
“…54% of the cross-section at the 5% height level, values somewhat higher than the 42% found by Gominho and Pereira [8] for 9-year-old E. globulus trees, but lower than the 73% found by Miranda et al [18] for 18-year-old E. globulus trees. This indicates the role of tree age in increasing the heartwood proportion as has been referred, too for E. grandis [2], Populus tremuloides [29], Pseudotsuga menziesii [13], Abies balsamea [11] and Pinus pinaster [21].…”
Section: Sitementioning
confidence: 67%
“…Heartwood volume (HV, cm 3 ) and sapwood volume (SV, cm 3 ): the HV and xylem volume (XV, cm 3 ) for each stem segment were calculated as a truncated cone by the Simpson formula (Pinto et al, 2004):…”
Section: Calculation Of Heartwood and Sapwood Parametersmentioning
confidence: 99%
“…Heartwood formation rate (HFR, rings y −1 ), heartwood initiation age (HIA, y) and heartwood initiation xylem radius (HIXR, cm): the slope of the function of HRN against CA represented the HFR (the rings transformed from sapwood to heartwood per year). The HIA was estimated by extrapolating the regressive curve of HRN against CA to zero HRN (Pinto et al, 2004). Similarly, the slope of the function of HR against XR represented the radial heartwood formation rate, and the extrapolation was HIXR.…”
Section: Calculation Of Heartwood and Sapwood Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have reported that wood density decreases with age or distance from the pith (Pinto et al 2004). This is supported by the fact that heartwood is usually known to be of a lower density than sapwood.…”
Section: Discussionmentioning
confidence: 98%